Career Preferences of Late Millennials and Z in Indonesia: Job Mobility, Aspirations, and Value Priorities - Sulastri Sulastri; Mira Yona; Hanafi Siregar; Hary Rangga; Nuur Faris Akram (Journal of Economics and Management Scienties, 2026)
This study examines differences in career preferences between Generasi 90-an (late Millennials, 1990–1996) and Generation Z (1997–2005) in Indonesia, focusing on job mobility, aspirations, and value priorities. Drawing on national surveys, industry reports, and recent scholarly literature (2022–2026), the findings indicate that generational orientations are shaped by distinct socio-economic experiences. Generasi 90-an tend to prefer stable and linear career paths, prioritizing financial security, organizational commitment, and structured advancement within formal sectors such as corporations, civil service, and state-owned enterprises. In contrast, Generation Z exhibits higher job mobility, with average tenure of 1–2 years, alongside greater acceptance of hybrid work and gig-based arrangements. This cohort places stronger emphasis on work-life balance, personal development, and intrinsic motivation. Although both groups value competitive compensation, Generation Z integrates well-being and alignment of personal values more explicitly into career decisions. Evidence from Surakarta also suggests variations across regions and definitions. These findings underscore the importance of adaptive talent management strategies, including flexible career pathways, hybrid work systems, and cross-generational engagement to sustain workforce effectiveness.